A closer look at the role of mentor teachers in shaping preservice teachers' professional identity. (November 2015) - Izadinia, Mahsa
Abstract: This paper focuses on the extent to which mentoring relationships played a role in creating changes in the professional identity of seven preservice teachers. Semi-structured interviews, observations and reflective journals were used to document the changes experienced by participants as they went through their two placements during their one-year teacher education course. The data indicated that when the mentoring relationships were positive and expectations were met, preservice teachers felt more confident as a teacher. However, for some participants, who experienced a partially negative mentoring relationship, their confidence declined and they felt they did not improve. Implications for practice are discussed. Highlights: The impact of mentoring relationship on professional identity of seven preservice was examined. When the mentoring relationship was positive the confidence level grew in the participants. But some participants experienced negative mentoring relationship and they felt less like a teacher at the end of the course.